A COMPARATIVE STUDY IN THE DIABETES MELLITUS PATIENTS FOR ORAL MANIFESTATION AT TERTIARY CARE HOSPITAL IN NORTH KARNATAKA - Nimbal, Anand V; Desai, Vikas C; Rathod, Shardha Bai (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Diabetes mellitus is the leading health problem across the world. It is associated with several complications such as retinopathy, neuropathy, oral manifestations, chronic macrovascular and microvascular complications. Our objective is to compare these oral manifestations in controlled and uncontrolled diabetic patients. Methods: A study was conducted on total of 100 diabetic patients. The patients were divided into two groups: Group I (n=50) consists of controlled diabetic patients and Group II (n=50) consists of uncontrolled diabetic patients. Before, the start of the study proper oral examination was done for both the groups. Samples were collected and were subjected to microbial examination. Comparison between both the groups was done for oral manifestations. Results: It showed that uncontrolled diabetic patients had a higher incidence of oral manifestations such as hyposalivation, parotid enlargement, burning sensation of mouth, taste alterations, sialorrhea, dental carries, and microbial lesions than controlled diabetes patients. Conclusion: Uncontrolled diabetic patients had higher risk of oral manifestations than controlled diabetic individuals. Keywords: Diabetes mellitus, Retinopathy, Neuropathy, Oral manifestations, Periodontitis, Hyposalivation.